Analysis Of Adverbial Constructions In The Selfish Giant By Oscar Wilde - DEWI, SEPTIKA PUSPA; , Dra. Malikatul Laila, M.Hum; , Dra. Siti Zuhriah Ariatmi, M.Hum (2015)
The aims of this research are to describe the types of adverbial constructions and to describe the distributions of adverbial constructions based on structural approach especially syntactic structure of modification. The data are taken from adverbial constructions found in "The Selfish Giant" short story by Oscar Wilde. The type of the research is descriptive qualitative research. In collecting data, the writer uses observation and documentation method by applying the techniques of identifying, classifying, analyzing and coding the data found. In analyzing data, the writer uses the theory of Allshop (1990) the forms of adverbial and its distributions. The writer finds 195 data of adverbial constructions in sentences of The Selfish Giant short story. The result of this research shows that the types of adverbial constructions are adverb of manner 5 or 3 %, adverb of place and direction 32 or 16 %, adverb of time 14 or 7 %, adverb of degree 10 or 5 %, adverb of frequency 5 or 3 %, conjunctive adverb 5 or 3%, noun phrase of time 9 or 5 %, to infinitive phrase 3 or 2 %, adverb phrase of manner 3 or 2 %, prepositional phrase of time 10 or 5 %, prepositional phrase of place 64 or 33 %, prepositional phrase of accompaniment 5 or 3 %, prepositional phrase of manner 7 or 4 %, adverbial clause of time 18 or 9 %, adverbial clause of cause 1 or 1 %, adverbial clause of purpose 1 or 1 %, adverbial clause of manner 1 or 1 %, adverbial clause of degree 2 or 1 %. Moreover, there are three distributions of adverbial constructions are initial position, mid- position and final position. Keywords: Adverbial Constructions, Structural Approach, The Types of Adverbial Constructions, The Distributions of Adverbial Constructions